Effects of a Type I RM System on Gene Expression and Glycogen Catabolism in Synechocystis sp. PCC 6803 - Wu, Dongqing; Wang, Yali; Xu, Xudong (Frontiers in Microbiology, 2020)
Increasing evidence has shown that DNA methylation is involved in gene regulation in prokaryotes. However, there have been very limited reports about the role of DNA methylation in regulation of gene expression and physiological functions in cyanobacteria. In Synechocystis sp. PCC 6803, four genes on the plasmid pSYSX are predicted to encode the type I restriction-methylation system, slr6095 and slr6096 for the M subunit, slr6097 for the S subunit and slr6102 for the R subunit. Compared to the wild type, slr6095, slr6096 and slr6097 mutants lacked the GGm6AN7TTGG/CCAm6AN7TCC methylation in genomic DNA. Transcriptomic analysis indicated that 171 genes were reproducibly up- or down-regulated in all three mutants relative to the wild type. The changed expression of some genes, including sll1356 for glycogen phosphorylase (GlgP), was associated with the loss of GGm6AN7TTGG/CCAm6AN7TCC methylation in the coding regions or the upstream non-coding sequences. Inactivation of slr6095, slr6096 or slr6097 increased the expression of sll1356 and the GlgP activity but lowered the glycogen content. These results indicated that the DNA methylation by a type I RM system could alter the expression of certain genes and physiological functions in Synechocystis sp. PCC 6803.